Pengaruh Kepercayaan Merek Terhadap Minat Beli KonsumenProduk Redmi di Kota Bima - Defrankan Defrankan; Sri Ernawati; Amirul Mukminin (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of brand trust on consumers' purchase intention toward Redmi products in Bima City. The research employed a quantitative approach with an associative research design. The population consisted of consumers who had purchased and used Redmi products in Bima City, while the sample comprised 50 respondents selected through purposive sampling. Data were collected through observation, questionnaires, and literature review, and analyzed using validity and reliability tests, simple linear regression, correlation coefficient, coefficient of determination, and t-test with the assistance of SPSS 22. The results indicate that brand trust has a positive and significant effect on consumers' purchase intention toward Redmi products in Bima City. This is evidenced by a regression coefficient of 0.946, a t-value of 9.735, which is greater than the t-table value of 2.011, and a significance value of 0.000 (<0.05). The correlation coefficient of 0.815 indicates a very strong relationship, while the coefficient of determination (R²) of 0.664 shows that brand trust explains 66.4% of the variance in purchase intention, with the remaining 33.6% influenced by other factors not examined in this study. Therefore, strengthening brand trust can significantly increase consumers' purchase intention toward Redmi products in Bima City.